Bancos de capacitores se corrente de Inrush - Pedrazoli, Guilherme Zorzi [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work discusses about the effects and methods of control and elimination of the currents transients generated by switching capacitor banks, this currents are called inrush currents. Capacitor banks are widely used to compensate a low power factor generated by the widespread use of inductive loads. Currently many of these banks are automatic and therefore the capacitive cells are connected and disconnected according to the inductive loads on the network. However when connecting a capacitor bank to a bus can generate currents transients generated by electromagnetic transients. Aspects of the network, for example, the existence of a bank already connected to the bus, can influence the intensity of this phenomenon. This paper discusses some characteristics of the capacitors and the network to justify and explain the appearance of these transients and discusses its effects on the network and to other equipment. It is concluded that the main cause of this phenomenon is the voltage difference between the capacitor to be connected to the network and the bus, the results of the study were the bases to discuss the traditional methods to mitigate these currents and therefore its negative effects. Although in this paper is yet developed a method of electronic switching that can greatly reduce these transients

Este trabalho trata dos efeitos e métodos de controle e eliminação das correntes transitórias geradas pelo chaveamento de bancos de capacitores, denominadas correntes de inrush. Bancos de capacitores são largamente usados para compensar um baixo fator de potencia gerado pelo amplo uso de cargas indutivas. Atualmente muito destes bancos são automáticos e desta forma as células capacitivas são conectadas e desconectadas de acordo com as cargas indutivas presentes na rede. Entretanto ao se conectar bancos de capacitores em um barramento pode-se gerar correntes transitórias, geradas por transitórios eletromagnéticos. Aspectos da rede como, por exemplo, a existência de um banco já conectado ao barramento, podem influenciar na intensidade deste fenômeno. Este trabalho aborda algumas características dos capacitores e da rede para justificar e explicar o aparecimento destes transitórios bem como discute seus efeitos para a rede e outros equipamentos. Conclui-se que a principal causa deste fenômeno é a diferença de potencial existente entre o capacitor a ser conectado e a rede, com o resultado do estudo foi possível discutir os métodos tradicionais para a mitigação destas correntes e conseqüentemente seus efeitos negativos. Ainda foi desenvolvido um método de chaveamento eletrônico capaz de diminuir drasticamente os transitórios
Keywords: Capacitadores; Correntes eletricas; Transitorios (Eletricidade); Eletrotecnica; Fator de potencia; Inrush Current; Electromagnetic transients